The Confusion of Tongues as Analyzed in Frank O’ Connor’s My Oedipus Complex - Pasopati, Rommel Utungga; Pangestu, Imelza Novia Rakhmadani; Wijaya, Kusuma; Hariyono; Kartiningsih, Rindrah (Universitas Tidar, 2024)
Confusion of Tongues stated by Sándor Ferenczi to show problematic relations between adults and children. He asserts traumatism, done by adults and experienced by children, may shape different perceptions in process. Emphasized by psychoanalysis, desire of love is so dominating that could result to violence. My Oedipus Complex is Frank O’ Connor’s short story that features perfect relationship of a child named Larry and his mother that is disturbed by return of his father from war. The mother tells his father as a puzzle then he becomes enemy for Larry for taking mother’s side. The child’s purity shifted into hate; from being accompanied to lonely and from being close to having distance. So, how is confusion of tongues analyzed in Frank O’ Connor’s My Oedipus Complex? Through qualitative method on Ferenczi’s perspective, this paper indicates psychoanalytic understandings in how language of mother disconcerted by child. The passion of love may break the heart of a child who loses that. Language of desire is reflection of not only giving but also obsessing and possessing. In conclusion, underlining confusion of tongues explains how passion could affect child differently. Any determination of love could always be misinterpreted especially through losing it.